Tendencias de la fecundidad en Aragón - Faus Pujol, María Carmen (Geographicalia, 2017)
The demographic future of Aragon is very involved as explain the main fertility indicators calculated, for this region. The present negative trend is owing to historical factors and, overcoat nowadays, behaviour factors related vith nuptiality and procreation.